Simultaneous Distal Radius Fracture with Acute Radial Artery Injury: Is it a Unique Complex Injury or a Misdiagnosis Lesion? - G, Kastanis; A, Pantouvaki; G, Magarakis; C, Chaniotakis; C, Christoforidis; P, Kapsetakis (International Journal of Innovative Research in Medical Science, 2021)
In spite of the fact that distal radius fractures are one of the most common injuries in emergency department, when these injuries accompanied with radial artery laceration, consist a very unique problem concerning the diagnosis as much as the treatment management. While many reports exist in literature which present the vascular complication of radial artery after surgical management of distal radius fracture, only three studies analyzed this complex injury. The qualified treatment of isolated DRF has been clarified but when the fracture is associated with radial artery lesion the protocol of treatment remains unclear. The aim of this study is to analyze three cases with simultaneous injuries of DRF and radial artery and to analyze our results compared to those presented in literature referring to the incidence of rate and treatment management.